2016
DOI: 10.1007/s00247-016-3741-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance tissue phase mapping demonstrates altered left ventricular diastolic function in children with chronic kidney disease

Abstract: Tissue phase mapping is feasible in children and adolescents. Children with chronic kidney disease show significantly reduced peak diastolic long- and short-axis left ventricular wall velocities, reflecting impaired early diastolic filling. Thus, tissue phase mapping detects chronic kidney disease-related functional myocardial changes before overt left ventricular hypertrophy or echocardiographic diastolic dysfunction occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
3
1
0
2
Order By: Relevance
“…Early diastolic peak velocity is a marker of both active relaxation and ventricular compliance [ 31 ]. Our demonstration of lower E’, measured using TPM, is in keeping with a previous smaller study in pediatric CKD [ 32 ]. In our study, E’ did not correlate with MVR or LVMht 2.7 .…”
Section: Discussionsupporting
confidence: 91%
“…Early diastolic peak velocity is a marker of both active relaxation and ventricular compliance [ 31 ]. Our demonstration of lower E’, measured using TPM, is in keeping with a previous smaller study in pediatric CKD [ 32 ]. In our study, E’ did not correlate with MVR or LVMht 2.7 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the present study is the first to investigate both LV and RV myocardial motion with TPM in children. Compared with previously studied healthy children of younger age (38,39), LV peak velocities in this study were reduced, which agrees with the reported age dependency. Similar to our findings, prior studies demonstrated significantly decreased LV peak velocities in older subjects (28,32).…”
Section: Discussionsupporting
confidence: 90%
“…All healthy controls used in this study had normal global LV and RV function with decreased indexed volumes for adults in agreement with literature (51). Of note, this study included children, which have been rarely studied with TPM (38,39). In addition, the present study is the first to investigate both LV and RV myocardial motion with TPM in children.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Trabalhos realizados em crianças e adolescentes com DRC identificaram a hipertrofia ventricular esquerda, a hipertensão arterial sistêmica e a disfunção diastólica como fatores de risco isolados para aumento da morbimortalidade cardiovascular 9,10 . Dentre esses, a disfunção diastólica parece ser a alteração mais precoce, como demonstrado em estudos que utilizaram ecocardiograma e ressonância nuclear magnética 11,12 .…”
Section: Introductionunclassified